2016
DOI: 10.1007/s00381-016-3281-1
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid (CSF) shunting and ventriculocisternostomy (ETV) in 400 pediatric patients. Shifts in understanding, diagnostics, case-mix, and surgical management during half a century

Abstract: ObjectiveTo characterize shifts from the 1960s to the first decade in the 21st century as to diagnostics, case-mix, and surgical management of pediatric patients undergoing permanent CSF diversion procedures.MethodsOne hundred and thirty-four patients below 15 years of age were the first time treated with CSF shunt or ETV for hydrocephalus or idiopathic intracranial hypertension (IIH) in 2009–2013. This represents our current practice. Our previously reported cohorts of shunted children 1967–1970 (n = 128) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 27 publications
(33 reference statements)
1
5
0
Order By: Relevance
“…In this study, shunt survival was poorest in the PHH group, with revision rates and number of revisions beyond a year and within 5 years significantly higher in PHH than in congenital or “other” hydrocephalus. This is consistent with Paulsen et al who demonstrated more frequent revisions in the PHH group than other aetiologies, and Notarianni et al who similarly showed higher 5-year shunt failure rates in PHH compared to congenital and “other” hydrocephalus, with no significant differences between PHH and myelomeningoceles [ 6 , 20 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In this study, shunt survival was poorest in the PHH group, with revision rates and number of revisions beyond a year and within 5 years significantly higher in PHH than in congenital or “other” hydrocephalus. This is consistent with Paulsen et al who demonstrated more frequent revisions in the PHH group than other aetiologies, and Notarianni et al who similarly showed higher 5-year shunt failure rates in PHH compared to congenital and “other” hydrocephalus, with no significant differences between PHH and myelomeningoceles [ 6 , 20 ].…”
Section: Discussionsupporting
confidence: 88%
“…The congenital and "other" hydrocephalus groups had significantly more "0 s" (normal outcome) than PHH at every time point (except 10 years for "other") (p < 0.01), and significantly fewer "3 s" than PHH at 5 and 10 years (p < 0.01). PHH, post-haemorrhagic hydrocephalus; NTDs, neural tube defects; NDO, neurodevelopmental outcome other aetiologies, and Notarianni et al who similarly showed higher 5-year shunt failure rates in PHH compared to congenital and "other" hydrocephalus, with no significant differences between PHH and myelomeningoceles [6,20].…”
Section: Surgical Outcomementioning
confidence: 98%
“…Furthermore, the demonstrated effect of NEL to lower CSF protein concentration has been used prior shunt implantation [24]. The overall shunt revision-free survival rate of 66.7% and a patient rate of 28.8% from 72 infants who needed revision within the first year is acceptable for this high-risk cohort of neonates [25][26][27]. On contrary to the rather effective treatment of hydrocephalus by CSF diverting shunt, the failure of all performed ETVs (n = 6) to permanently control a hydrocephalic situation reflect the previously published experiences after this operative procedure in very young children [4].…”
Section: Discussionmentioning
confidence: 99%
“…If treated today, these patients might have been candidates for modern radiotherapy at tumor progression. The latter late death was caused by an acute shunt failure which is exceedingly rare, but the risk of such failure is impossible to fully eliminate [ 12 ]. The fact that 72% of long-term survivors in this LG tumor group had full-time working capacity is important and very interesting.…”
Section: Discussionmentioning
confidence: 99%